Exploring business strategies and brand identity for Tuku among local small coffee shops in the era of global competition - Ambarwati, Ambarwati; Angelica, Agnes Meylisa; Ananditha, Mutiara (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2026)
The objective of this study is to explore the business strategies and brand identity implemented by Coffee Tuku in responding to the dynamics of global competition. This research also aims to identify the key success factors that enable Coffee Tuku to build a sustainable competitive advantage grounded in local values and culture. This study employs a descriptive qualitative approach using in-depth interviews, direct observation, and secondary documentation as data collection methods. Data analysis is conducted using the SWOT framework to identify business strengths, weaknesses, opportunities, and threats, as well as the Brand Identity Prism model to examine the dimensions that shape brand identity. The findings indicate that Coffee Tuku adopts a value-based differentiation strategy by emphasizing authenticity of taste, simplicity, and social relationships with customers. Tuku’s brand identity is primarily constructed through the dimensions of culture and relationship, reflecting values of mutual cooperation (gotong royong), social closeness, and pride in local products. The synergy between business strategy and brand identity serves as the source of Coffee Tuku’s competitive advantage amid increasingly homogeneous global competition.